Adsorptive removal of Cr (VI) from aqueous solution using laboratory prepared ZnO nanoparticles - Rajbhandari Nyachhyon, Armila; Pote Shrestha, Rojita (Scientific World, 2023)
Nano sized zinc oxide (ZnO) been successfully prepared in laboratory by precipitation technique. As prepared ZnO materials were characterized by XRD and SEM analyses. The XRD pattern showed the crystallinity of the material and average crystallite size was found to be 16.61 nm. The SEM images of ZnO nanoparticle revealed that it was flakes like structure having smooth texture. Batch adsorption experiments were performed to investigate the percentage removal of Cr (VI) from aqueous solution. The effects of Cr (VI) concentration, pH of solution, adsorbent dose and contact time variations were studied in order to have adsorptive efficiency of as prepared ZnO nanoparticles. The optimum contact time for maximum adsorption was found to be 90 minutes. The optimum pH was found to be 2.0 at an initial concentration of 20 mg/L. Similarly, the optimum dose of ZnO for the adsorption of Cr (VI) was found to be 0.4 g. The adsorption properties of ZnO were then evaluated by using Langmuir, Freundlich and Temkin isotherm models. The maximum adsorption capacity (Qm) was found to be 3.43 mg/g which is in good agreement with literature value. The correlation value showed that Langmuir isotherm model was found to be more favorable than Freundlich and Temkin adsorption isotherm model, indicating the presence of homogeneous equivalent active sites in ZnO with monolayer adsorption.